Legal Reform in Occupied Japan : A Participant Looks Back - Oppler, Alfred C. (Alfred Christian), 1893-1982 (Book collections on Project MUSE., 1976)
After a distinguished career as a jurist in Germany, Alfred Oppler came to the United States in 1939, and in 1946 was invited to Tokyo, where he was SCAP's authority on reform of the Japanese legal order to implement the principles of the new Constitution. Here is his account of the legal reforms and the methods used to achieve them. The author describes the wide scope of his activities, which included a vigorous promotion of civil liberties, surveillance of relevant legislation, and observation of the administration of justice throughout the country. He focuses on the Continental nature of the Japanese law and analyzes the American objectives as well as the personalities of the Occupation and of Japanese with whom he negotiated. Special chapters describe the Supreme Court mission to the United States (which the author escorted), the removal of General MacArthur, and the author's post-Occupation work on Japanese, Korean, and Ryukyuan problems. Treating all aspects of the legal reforms, this book provides insights into Japan during and after the Occupation.Originally published in 1976.The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press. These editions preserve the original texts of these important books while presenting them in durable paperback and hardcover editions. The goal of the Princeton Legacy Library is to vastly increase access to the rich scholarly heritage found in the thousands of books published by Princeton University Press since its founding in 1905.